Computer modelling of movement of meat raw material on pipelines - Litovchenko, Igor; Taran, Vitaly; Beseda, Sergey; Hadzhіyskі, Vіlhelm; Stefanov, Stefan (My University, 2011)
In the present study we investigated methods for determining the design parameters of the pipeline for pneumatic transport with the use of modern computer systems engineering analysis. An integrated approach is proposed for the determination of geometric and strength parameters of the process equipment. Based on the previously established three-dimensional model of the pipeline is proposed by means of CAD systems to model the movement of the product at different sites. Using a simulation based on computer calculation methods, improving the accuracy of the results. Modeled dvidenie raw materials in several tribes of the radius from 80 mm to 250 mm with a certain step of the radius. As a result, modeling the values ​​of pressure. With their help, we can determine the required compressor power.
Keywords: modeling; simulation; pipeline; pneumatic transport; моделирование; имитация; трубопровод; пневмотранспорт; імітація; моделювання; трубопровід; пневмотранспорт; кафедра машин і апаратів харчових та фармацевтичних виробництв